ZAKAT LITERACY INDEX AS A TAXABLE INCOME DEDUCTION (A STUDY CASE IN SIDOARJO) - Mochammad Imanda Ramadhani; Clarashinta Canggih (IAIN Manado, 2023)
This study aims to measure the literacy on zakat as a deduction from taxable income in Sidoarjo. This study uses a quantitative descriptive method an adapted Zakat Literacy Index by BAZNAS to measure the zakat as a taxable income deduction literacy index. The data used in this study was questionnaires about the literacy rate of the people of Sidoarjo. This study uses primary data sources or is collected through questionnaires directly to respondents. The sample used must be a Muslim and have a Taxpayer Identification Number (NPWP) because the measured variable is zakat literacy level as a deduction from taxable income, which is an obligation for a Muslim who has accumulated wealth beyond a certain threshold and is required to pay zakat. There are two dimensions included inthe literacy index of zakat as a taxable income deduction, i.e., a basic understanding of the relationship between zakat and taxes with 4 variables and an advanced understanding of the relationship between zakat and taxes with 3 variables. The findings showed that the literacy level of zakat as the deduction of taxable income in Sidoarjo is moderate which means the society has understood the obligation to pay zakat and taxes, as well as how to fulfill the payment process. The lowest score in the basic dimension is understanding the legal basis of zakat and tax, and in the advanced dimension is understanding the socialization program. The lowest score in each dimension follows the result of the literacy level of zakat in Indonesia that BAZNAS conducted.